2022
DOI: 10.1136/heartjnl-2022-321196
|View full text |Cite
|
Sign up to set email alerts
|

Eligibility for early rhythm control in patients with atrial fibrillation in the UK Biobank

Abstract: ObjectiveThe Early Treatment of Atrial Fibrillation for Stroke Prevention (EAST-AFNET4) trial showed a clinical benefit of early rhythm-control therapy in patients with recently diagnosed atrial fibrillation (AF). The generalisability of the results in the general population is not known.MethodsParticipants in the population-based UK Biobank were assessed for eligibility based on the EAST-AFNET4 inclusion/exclusion criteria. Treatment of all eligible participants was classified as early rhythm-control (antiarr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 20 publications
0
21
0
Order By: Relevance
“…The safety of ERC has been replicated in several analyses of large record data sets in South Korea, 17 the USA, 5 and in the UK BioBank. 6 Consistent with our observation, randomization to the antiarrhythmic drug dronedarone was associated with reduced cardiovascular mortality and less ischaemic strokes (HR 0.66; 95% CI 0.45–0.96) in a subanalysis of the ATHENA trial (a placebo-controlled, double-blind, parallel arm trial to assess the efficacy of dronedarone 400 mg twice daily for the prevention of cardiovascular hospitalization or death from any cause in patients with AF/atrial flutter), 18 in addition to reducing a primary outcome of death or cardiovascular hospitalization. 19 Even the lack of effectiveness of dronedarone in the subsequent PALLAS study, where dronedarone therapy without restoration of sinus rhythm was associated with worse cardiovascular outcomes, can be aligned with our analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The safety of ERC has been replicated in several analyses of large record data sets in South Korea, 17 the USA, 5 and in the UK BioBank. 6 Consistent with our observation, randomization to the antiarrhythmic drug dronedarone was associated with reduced cardiovascular mortality and less ischaemic strokes (HR 0.66; 95% CI 0.45–0.96) in a subanalysis of the ATHENA trial (a placebo-controlled, double-blind, parallel arm trial to assess the efficacy of dronedarone 400 mg twice daily for the prevention of cardiovascular hospitalization or death from any cause in patients with AF/atrial flutter), 18 in addition to reducing a primary outcome of death or cardiovascular hospitalization. 19 Even the lack of effectiveness of dronedarone in the subsequent PALLAS study, where dronedarone therapy without restoration of sinus rhythm was associated with worse cardiovascular outcomes, can be aligned with our analysis.…”
Section: Discussionmentioning
confidence: 99%
“… 5 , 6 Based on the inclusion criteria of the EAST-AFNET 4 trial, the majority of patients with new-onset AF are eligible for ERC. 6 The results have started to shift the use of rhythm control therapy from a symptom-driven therapy to a risk-reducing strategy aiming at restoring and maintaining sinus rhythm as the default therapy in patients with recently diagnosed AF and stroke risk factors. 7 , 8 …”
Section: Introductionmentioning
confidence: 99%
“…The application of a clinical risk model ( Figure S1 ) could optimize the selection of candidates for screening even further, and early anticoagulation and early treatments such as cryoablation or drug therapy [ 67 ] may modify the chronic progression of atrial fibrillation, lowering stroke risk rates. Around 80% of the participants diagnosed with AF in the United Kingdom population are eligible for early cardiac rhythm control [ 68 ], and the implementation of new digitalhealth technologieshas the potential to improve outcomes by facilitating self-management and by enabling earlier detection and intervention for adverse events [ 69 , 70 , 71 ]. Finally, the use of artificial intelligence (AI) approaches in stroke risk prediction showed a significant ability to predict the risk of stroke occurrence, but it did not significantly improve discriminative accuracy for new-onset stroke compared with pooled cohort equations [ 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…No additional studies were found in the reference lists of previous reviews [17,18]. Finally, a total of 8 studies [8,[10][11][12][19][20][21][22] (1 RCT [8], 2 post hoc analyses of RCTs [11,12], and 5 observational cohorts [10,[19][20][21][22]) were included in this meta-analysis.…”
Section: Study Identification and Selectionmentioning
confidence: 99%
“…In addition, the modest number of included studies limited the application of other techniques to tease out potential contributors (e.g., meta-regression based on population age, study period). Second, we did not consider safety outcomes because only two included studies (Kirchhof et al and Kany et al) [8,20] fully presented serious adverse events, suggesting that the safety outcomes did not differ between early rhythm-control therapy and usual care. In addition, the quality of life was not considered in our study because it was assessed as outcome in two included studies (Kirchhof et al and Proietti et al).…”
Section: Limitations Of This Studymentioning
confidence: 99%